Housing bubble in China. - Foong, Siao Thong. (2013)
Ever since the implementation of China’s housing reform in 1998, the high and rapidly rising housing prices has led to increasing concerns, by the Chinese government and its regulators. This paper aims not only to illustrate the presence of bubble, but also, to estimate the size of bubble, which is of paramount importance to effective policy tools and introductions as well as for further studies on its causes. By using fundamental price model by Christian Hott and Terhi Jokipii (2012), we seek to calibrate the fundamental price of housing in 35 Chinese cities, for comparison against the actual housing prices to deduce the degree of overvaluation or undervaluation. Our paper also discusses possible approach that the Chinese government could take to counter the issue of its housing bubble.